PENATALAKSANAAN TEKNIK PEMERIKSAAN BNO IVP PADA KASUS URETEROLITHIASIS DI INSTALASI RADIOLOGI RUMAH SAKIT PEKANBARU MEDICAL CENTER - Hadits Chairunnisa Fadillah Nugroho (LPPM Universitas Awal Bros, 2024)
CT Scans can be used as a supporting tool to identify abnormalities and determine certain clinical conditions, one of which is abdominal examination to maintain a clinical diagnosis such as abdominal colic. In this article, a CT Scan examination procedure has been carried out in cases of abdominal colic in the Hospital Radiology installation. Islam Ibn Sina Pekanbaru. This study aims to determine the abdominal CT Scan examination process in cases of abdominal colic and to determine abdominal scans in cases of abdominal colic at the Radiology Installation of the Ibnu Si Islamic Hospital Pekanbaru. Method: The type of research used in this research is a qualitative researcher with a case study approach. Results: The results of the study showed that CT Scans in cases of abdominal colic at the Ibnu Sina Islamic Hospital Pekanbaru installation could be performed without contrast and the patient was positioned head first. Conclusion: CT Scan diagnostic information in cases of adenomenal colic is able to provide indicative information